The South Atlantic Anomaly: The Key for a Possible Geomagnetic Reversal - Pavón-Carrasco, F. Javier; De Santis, Angelo (Frontiers in Earth Science, 2016)
The South Atlantic Anomaly is nowadays one of the most important features of the Earth’s magnetic field. Its extent area at the Earth’s surface is continuously growing since the intensity instrumental measurements are available covering part of the Southern Hemisphere and centred in South America. Several studies associate this anomaly as an indicator of an upcoming geomagnetic transition, such an excursion or reversal. In this paper we carry out a detailed study about this issue using the most recent models that also include data from the last ESA mission Swarm. Our results reveal that one of the reversed polarity patch located under the South Atlantic Ocean is growing with a pronounced rate of -2.54•105 nT per century and with western drift. In addition, we demonstrate that the quadrupole field mainly controls this reversal patch at the CMB along with the rapid decay of the dipolar field. The presence of the reversal patches at the CMB seems to be characteristic during the preparation phase of a geomagnetic transition. However, the present value of the dipolar moment (7.7 1022A•m2) is not so low when compared with recent paleomagnetic data for the Holocene (last 12ka) and for the entire Brunhes geomagnetic normal polarity (last 0.8 Ma), although the rate of decay is similar of the previous documented geomagnetic reversals or excursions.